Dynamic Contrast-Enhanced Ultrasound (DCE-US) for the Characterization of Hepatocellular Carcinoma and Cholangiocellular Carcinoma - Wildner, D.; Pfeifer, L.; Goertz, R. S.; Bernatik, T.; Sturm, J.; Neurath, M. F.; Strobel, D. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: In a prospective study, we compared the different perfusion kinetics of HCC and ICC using dynamic contrast-enhanced ultrasound (DCE-US).Materials and Methods: Patients with proven HCC and ICC were included. Three-minute video clips of CEUS examinations (CPS – low MI mode) after a bolus injection of 1.2 ml SonoVue® were recorded and analyzed with quantification software (VueBox®). Parameters for the arterial contrast enhancement [rise time (RT), time-to-peak (TTP)] towards portal venous contrast enhancement [mean transit time (local) (mTTl) and fall time (FT)] were quantified. Furthermore, contrast wash-out after peak enhancement (PE) (40 s, 80 s, 100 s and 120 s after PE) was compared between HCC and ICC.Results: 43 patients with proven HCC (n = 23 HCC; cirrhosis n = 16) and ICC (n = 20 ICC; Cirrhosis n = 6) were examined. No statistical difference of the arterial DCEUS parameters was found between HCC and ICC. Contrast enhancement of the portal venous and late phases showed significantly lower values in the ICC group indicating early wash-out of the contrast agent: mTTl (p = 0.0209): HCC 118.4 s (SD± 88.4); ICC 64.8 s (SD± 49.7). FT (p = 0.0433): HCC 42.5 s (SD± 27.7); ICC 27.7 s (SD± 16.2). The percental loss of intensity at a definite time point after PE was significantly higher in ICC than in HCC lesions.Conclusion: DCE-US is able to detect and quantify differences in perfusion kinetics between HCC and ICC. Whereas arterial contrast enhancement patterns may overlap between HCC and ICC, a timed characterization of wash-out kinetics may offer an additional tool to characterize HCC and ICC. The presence of a rapid loss of signal intensity in the early portal venous phase is significantly higher in ICC than in HCC lesions.
Keywords: dynamic contrast-enhanced ultrasound (DCEUS); quantification; hepatocellular carcinoma; cholangiocellular carcinoma